Нейромаркетинг в основі маркетингових рішень: нове бачення поведінки клієнтів - Момотков, Ігор Сергійович (Видавничий дім "Гельветика", 2025)
У статті розглянуто теоретичні та прикладні аспекти використання нейромаркетингу в процесі прийняття маркетингових рішень. Обґрунтовано важливість впровадження нейротехнологій для підвищення ефективності комунікацій із цільовою аудиторією, персоналізації маркетингових стратегій і підсилення емоційної залученості. Розкрито складові парадигми нейромаркетингу: фундаментальну (теоретичну) та інструментальну (прикладну). Зазначено, що застосування інструментів нейровізуалізації дозволяє отримати точні емпіричні дані про реакції споживачів, що дає змогу будувати науково обґрунтовані маркетингові рішення. Окрема увага приділяється основним напрямкам впливу нейротехнологій у маркетингових стратегіях. Підкреслено роль нейромаркетингу в формуванні користувацького досвіду, особливо в цифрових платформах та соціальних мережах, де за допомогою Emotion AI та інших аналітичних інструментів можна моделювати індивідуалізовані шляхи взаємодії з користувачем. Introduction. In the context of rapid digital transformation and increasing competition in global markets, the study of consumer behaviour through the prism of emotional and cognitive responses has become a key challenge for marketers. Neuromarketing, a relatively new interdisciplinary fild, is gaining signifiant attention for its ability to provide deeper insights into consumers’ unconscious reactions and decision-making mechanisms. Purpose. The primary objective of this research is to demonstrate the relevance and practical applicability of neuromarketing tools in improving marketing decision-making processes, particularly in the area of personalised communication and emotional consumer engagement. Methods. The study is based on a synthesis of theoretical and empirical approaches to neuromarketing. A systematic analysis of the scientifi literature, the principles of neuroeconomics and applied neuromarketing technologies such as EEG (electroencephalography), eye tracking and facial expression analysis were carried out. Attention is also given to ethical issues arising from the use of neurotechnologies in commercial activities. Results. The results of the study show that the integration of neuromarketing tools enables marketers to better understand consumers’ hidden motives, emotional triggers and the effctiveness of advertising messages. The use of biometric and neurophysiological data helps to create more emotionally resonant content, which in turn increases the effctiveness of communication strategies, enhances brand loyalty and improves the overall user experience. In addition, the research highlights the growing role of emotion AI and neurointerfaces in real-time behaviour monitoring and feedback optimisation in digital environments. Conclusion. The author concludes that the implementation of neuromarketing tools is an effctive means of achieving competitive advantage in customer interaction. In particular, Ukrainian companies can benefi from adopting neurotechnologies to refie their communication models, tailor content to emotional responses, and increase customer satisfaction. Recommendations are made for incorporating neuromarketing approaches into the strategic planning of marketing activities, while maintaining transparency and ethical responsibility.
Neuromarketing as the basis for marketing solutions: a new vision of customer behaviour
Keywords: нейромаркетинг; поведінка; споживачі; маркетингові рішення; емоційний інтелект; нейротехнології; користувацький досвід; персоналізація; комунікації; neuromarketing; behaviour; consumers; marketing solutions; emotional intelligence; neurotechnology; user experience; personalisation; communication